The Developed Method for Evaluation of the Oil Spot of Engine Oil of Motor Vehicles by Comprehensive Criteria for Diagnostics of the Technical Condition of Engine Oil - Kholmirzaev Javlonbek; Masodiqov Jaxongirmirza (Zien Journals, 2022)
A technique has been developed for correcting the frequency of maintenance of an internal combustion engine of motor vehicles according to a complex criterion for diagnosing the technical condition of engine oil. The dependence of the frequency of oil change of motor vehicle engines on the developed complex criterion was determined
Keywords: Technical means; maintenance; labor intensity of technical impacts; motor vehicles